Dekonstruksi Perlakuan Akuntansi Dana Syirkah Temporer: Jebakan Hibriditas Dan Hegemoni Paradigma Utang-Ekuitas Konvension - Rakhmawan Habibi; Mohamad Nur Husen; Abdul Wakhid; Ahmad Zainul Abidin (Faculty of Islamic Economics and Business, 2026)
Temporary Syirkah Funds in Islamic banking present a fundamental anomaly to conventional accounting architecture. This study employs a Derridean deconstruction approach to unravel the metaphysical assumptions underlying the current accounting treatment of DST, which places it in a